THE ALIENATION OF LOCAL COMMUNITIES IN TOURISM VILLAGES: A STUDY ON THE OSING COMMUNITY TOURISM VILLAGE IN BANYUWANGI REGENCY - Ernando, Gesta Agam; Susilo, Anggun Trisnanto Hari; Kholifah, Siti (Universitas Negeri Medan, 2025)
Tourism is one of the key sectors in the local economy, especially in areas rich in culture and local wisdom like Banyuwangi Regency. Kemiren Village, inhabited by the Osing indigenous community, has been designated as a tourist village. However, the development of this tourist village often alienates the local community from the decision-making process, reducing their role and the benefits they should receive. This study aims to examine the involvement of the Osing community in the development of Kemiren Tourism Village and the impact of alienation on their economic, social, and cultural well-being. Based on Karl Marx’s theory of alienation, this study uses five indicators of alienation: powerlessness, meaninglessness, social isolation, normlessness, and self-estrangement. This theory helps to understand how communities feel disconnected from the processes and outcomes they should be involved in and benefit from. This research employs a qualitative approach with a case study method. Data collection was conducted through semi-structured interviews, observation, and document analysis. The informants include the village head, traditional leaders, and community members directly involved in the development of Kemiren Tourism Village. The findings show that the Osing community in Kemiren Village experiences alienation during the development of the tourist village. Although their involvement was minimal in the planning stage, positive adaptation was observed in the implementation phase, particularly in preserving local culture and boosting the economy through tourism activities. Active participation in the implementation stage reduces the sense of alienation, but more inclusive involvement is necessary to ensure a fairer distribution of benefits. More inclusive involvement and empowerment strategies focused on the local community are essential to reduce alienation and improve the economic, social, and cultural well-being of the Osing community in Kemiren Tourism Village. These findings provide a foundation for designing more sustainable and equitable tourism village development policies.